Digital Literacy and Reading Habits of the DMI-St. Eugene University Students - A, Subaveerapandiyan; Sinha, Priyanka (My University, 2022)
Digital literacy is the skill of finding, evaluating, consuming, and generating information using digital technologies. The study attempted to comprehend university students' digital reading habits and skills. It also provides a glimpse of the pupil's favourite reading materials, including physical and digital sources. We examined BSc and BE Computer Science students of DMI-St. Eugene University, Zambia. The tool was a structured questionnaire that was distributed through WhatsApp. The study's findings revealed that most students thoroughly understand digital tools and how to use them, but lack the skills to build their websites and portfolio. Out of 115 students, all agreed they used computers for learning purposes. Usage of digital environments, generally, they used the World Wide Web for searching for information. Additionally, most students have medium digital application skills, despite their preference for reading electronic books. The results indicate that students' gender and level of education had a statistically significant link with their digital literacy, whereas age wasn't shown to be a statistically relevant predictor. The findings show that, in terms of education, especially reading, students' or readers' top priorities are electronic resources; print book preferences are reduced.
Keywords: Reading Habits; E-Resources; Digital Literacy